The association between neutrophil to high-density lipoprotein cholesterol ratio and gallstones: a cross-sectional study - Yinkang Wang; Xingchen Shang; Yinchao Zhang; Yu Zhang; Wei Shen; Qian Wu; Wenyi Du (BMC Public Health)
Abstract Objective Several studies have discussed the relationship between cholesterol and gallstones, and high-density lipoprotein cholesterol (HDL-C) as a representative of this has been addressed in various diseases. The metric neutrophil to high-density lipoprotein cholesterol ratio (NHR) derived from HDL-C has attracted much attention. The purpose of this article is to examine the relationship between NHR and gallstones in a population of American adults. Methods This study investigated the correlation between NHR and gallstone prevalence among US adults using population-based data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES). NHR was derived by dividing the neutrophil count by HDL-C. Data were analyzed using a variety of statistical techniques, such as univariate analysis, multivariate analysis, and subgroup analysis. In addition, a receiver operating characteristic curve (ROC) was used to determine the predictive power of the index for the risk of gallstone prevalence. Results The trial enrolled 6,954 subjects, among whom 746 patients were diagnosed with gallstones. By fully adjusted multivariate logistic regression analysis in the Model 3 section observed a significant positive association between NHR and gallstones with an odds ratio (OR) of 1.05 and a 95% confidence interval (CI) of (1.01, 1.10). The restricted cubic curve (RCS) had a P-Nonlinear = 0.481, suggesting that the relationship was a near-linear one. The area under the curve (AUC) of the ROC curve was 0.550, indicating that NHR has a predictive value for the development of gallstones. Conclusion This study demonstrated a near-linear correlation between NHR and increased susceptibility to gallstones, and the ROC curve is evidence that NHR has some predictive value for the risk of gallstones, albeit with weak predictive power relative to NPAR (Neutrophil percentage/albumin) and NAR (Neutrophils/albumin). Of course, to confirm these findings, more extensive prospective studies are needed to thoroughly validate the role of NHR in the development of gallstones.